Experimental study of dynamic fracture behavior of Al7075-T651 under different loading rates. (December 2022) - Pandouria, Anoop Kumar; Kumar, Sanjay; Tiwari, Vikrant
Abstract: The dynamic fracture initiation toughness for an aluminium alloy, Al7075-T651, has been estimated experimentally at different loading rates of 6.20, 7.87, and 10.1 M P a m / μ s . In this study, dynamic 3-point bend experiments were performed with a modified Hopkinson Pressure Bar (MHPB) associated with two high-speed cameras. A 3D digital image correlation (DIC) technique was used to get the full-field deformation of the specimen, such as crack initiation time and crack mouth opening displacements. Load point displacement as well as crack mouth opening displacement methods were used to determine the stress intensity factor (SIF). It was discovered that the dynamic fracture toughness significantly increased with increasing loading rates. The fractography carried out on the surface of fractured samples revealed transgranular facets and large dimples, which illustrated an increase in the fracture toughness with loading rates. 2D and 3D profiles of fractured surface were drawn, which relate undulation with fracture toughness. Graphical Abstract: ga1